CHARACTERISTICS OF PRODUCTIVE SKILLS IN TEACHING FOREIGN LANGUAGE - Bekkulova Xojar Zayniddinovna; Xodjayorova Sayora Abdullaevna (International Journal of Innovations in Engineering Research and Technology, 2021)
The following article is dedicated to the importance of speaking in learning foreign language. The author considers some characteristics of speaking and introduces major tips of speaking skills in teaching foreign language.